Abortive substances and medicines used by adolescents in a secondary health care unit - doi:10.5020/18061230.2005.p177 - Barros, Francisca Rosana do Nascimento (2012)
Pregnancy in adolescence almost always occurs in an unexpected way. Many end up as induced abortion. The adolescents use medicines or teas as methods that can lead to abortion, congenital abnormalities, complications or even, death. The study aimed at identifying and analyzing the use of abortive medicines or other substances by adolescents; identifying also their motives for using them, their instruction degree and evaluating their knowledge level of the substances or medicines applied as abortive practice. It was a cross-sectional, descriptive, observational and qualitative study with a quantitative approach, in which a questionnaire was applied to forty adolescents, between 13 to 21 years old, randomly chosen at the Núcleo de Atenção Médica Integrada – NAMI gynecological prevention attendance and at its pediatric ambulatory, in the period of September 22 to October 10, 2003. The results showed that all the interviewed adolescents were literate. Among the interviewed young, ten related having used some substance or medicine to induce the abortion or to induce the menstrual cycle, for being pregnant or with suspicion of pregnancy. In the study, substances such as artificial grape juice, by itself or associated with “cachaça” and “pílula do mato”; the teas of kingdom pepper, “carrapicho”, “boa noite” and “quebra-pedra”; menstrual cycle regulators available in pharmacies and misoprostol, were refereed. Misoprostol continues to be used by the population, even after the great publicizing of its toxic effects and high rate of incomplete abortion.